Segmental Living Liver Transplantation as An Alternative Method - Mehmet HABERAL; Nebil BÜYÜKPAMUKÇU; Hasan TELATAR; Nevzat BİLGİN; Gülnaz ARSLAN; Halis ŞİMŞEK; Enver EKİCİ; Mualla KARAMEHMETOĞLU; Aytekin BESİM; Bedri UZUNALİMOĞLU; Burhan KAYHAN; Yusuf BAYRAKTAR; et al. (Turkish Journal of Gastroenterology, 2020)
-